A fast convergence method for optimal solution of transportation optimization problems in sustainable supply chain management - Putcha C.; Banerjee A.; Rana B.S. (My University, 2025)
This paper deals with a consolidated study for optimization of transportation problems formulated as linear programming problem. The proposed method provides optimal method with fast convergence of transportation problems. The advantage of the developed optimization method is that by making appropriate changes in initial basic feasible (IBF) solution, one can arrive at optimal solution, without the need to carry out iteration using chain reaction method or transportation simplex algorithm. The efficiency of proposed algorithm is illustrated through specific examples on transportation problems. Even though, the proposed method is applied here to few small scale problems, it will be extremely useful for solving large scale optimization problems encountered in many areas, including supply chain, green engineering and smart manufacturing. These concepts are used extensively in various disciplines like Industrial Engineering, Mechanical Engineering etc. © 2021 Alpha Publishers. All rights reserved.